2015
DOI: 10.1159/000441007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 24 CYP2D6 Variants Found in the Chinese Population on the Metabolism of Risperidone

Abstract: Aims: Cytochrome P450 (CYP450) 2D6 is an important member of the P450 enzyme superfamily and responsible for clearing 25% of clinically important drugs. The aim of this study was to assess the catalytic characteristics of 24 CYP2D6 allelic isoforms found in the Chinese population and their effects on the metabolism of risperidone in vitro. Methods: Insect microsomes expressing wild-type CYP2D6 and 24 CYP2D6 allelic variants were incubated with 20-1,000 μmol/l risperidone for 40 min at 37°C. After termination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
3
6
1
Order By: Relevance
“…Consequently, our results showed notably decreased intrinsic clearance of the 2 variants, 39.70% for CYP2D6 * 2 and 5.22% for CYP2D6 * 10 relative to wildtype. This was consistent with the investigation of dextromethorphan, bufuralol, venlafaxine, atomoxetine and risperidone in our laboratory [7,[27][28][29].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consequently, our results showed notably decreased intrinsic clearance of the 2 variants, 39.70% for CYP2D6 * 2 and 5.22% for CYP2D6 * 10 relative to wildtype. This was consistent with the investigation of dextromethorphan, bufuralol, venlafaxine, atomoxetine and risperidone in our laboratory [7,[27][28][29].…”
Section: Discussionsupporting
confidence: 91%
“…In our laboratory, CYP2D6 * 2 and CYP2D6 * 10 were used as controls for decreased function and exhibited 54.3-1.3% relative clearance [7,[27][28][29] (and this study). We supposed that alleles with the relative clearance less or close to CYP2D6 * 2 are more likely to indicate pharmacokinetic changes in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The latter amino acid substitution has been shown to cause protein instability and reduced substrate affinity (Wang et al, 1999). As reported by previous studies, CYP2D6.10 yields 1.34%-4.57% of the efficiency of CYP2D6*1 toward bufuralol (1.34%), propranolol (1.41%), risperidone (2.01%), venlafaxine (2.90%), and dextromethorphan (4.57%) in vitro (Liang et al, 2015;Wang et al, 2015;Cai et al, 2016;Zhan et al, 2016). In our study, CYP2D6.10 had a decreased V max (8.71%), an increased K m (3.62-fold), and a significantly decreased intrinsic clearance (4.07%) of nebivolol compared with CYP2D6.1.…”
Section: Resultssupporting
confidence: 65%
“…In a study of dextromethorphan and bufuralol, Dai et al (2015) suggested that L142S could impair enzymatic activity to some extent, resulting in extremely decreased intrinsic clearance values (,20%) of CYP2D6.1. In other studies, CYP2D6.89 exhibited markedly different catalytic activity toward venlafaxine (71.1%), methadone (74.62%), risperidone (87.56%), and atomoxetine (102.6%) compared with CYP2D6.1 (Wang et al, 2015;Liang et al, 2016;Su et al, 2016;Zhan et al, 2016). Our data revealed that this variant showed no significant difference compared with the wild type but showed a trend of substrate inhibition (Fig.…”
Section: Resultssupporting
confidence: 48%
“…We validate the genotype-based activity predictor and star allele classifier using in vitro data from literature. We identified two sets of studies to use for validation: (1) a functional characterization of 49 CYP2D6 star alleles performed using three substrates, and (2) eight in vitro studies of eleven CYP2D6 star alleles discovered in Han Chinese subjects using ten substrates [45][46][47][48][49][50][51][52][53][54] . We exclude fourteen star alleles which were found in our training data, and evaluate on measurements for 46 star alleles that were not in our training data.…”
Section: Literature Validationmentioning
confidence: 99%